The significance of language exposure with writing self-efficacy and writing apprehension of Filipino ESL writers - Pariña, Jose Cristina M. (Animo Repository, 2013)
The study investigated the relationship of English language exposure, writing apprehension and writing self-efficacy of 64 college students taking up academic writing. Instruments used were the language exposure questionnaire, the writing apprehension test or WAT by Daly-Miller, which was used in the study of Erkan and Saban (2011), and the self-efficacy in writing scale questionnaire (SWS) by YaVuz– Erkan (2004, as cited in Erkan & Saban, 2011). Pearson r was utilized in the analysis of the relationship of the mentioned variables and results of the study show that first, exposure and self-efficacy are moderately correlated, which means that the respondents who have more access or exposure to the target language felt more confident in their writing outputs. Second, the exposure and self-apprehension are not correlated, which means that apprehension is possible despite high exposure to the language. Lastly, writing self-efficacy and writing apprehension are inversely correlated, which means that the higher the self-efficacy, the lower the apprehension and vice versa.